Highly efficient and stable inverted perovskite solar cells using down-shifting quantum dots as a light management layer and moisture-assisted film growth. Issue 24 (5th June 2019) - Tavakoli, Mohammad Mahdi; Dastjerdi, Hadi Tavakoli; Prochowicz, Daniel; Yadav, Pankaj; Tavakoli, Rouhollah; Saliba, Michael; Fan, Zhiyong
Abstract : Down-shifting QDs together with moisture-assisted film growth enable a highly efficient and stable inverted perovskite solar cell with efficiency of over 20%. Abstract : Stability is one of the key challenges for perovskite solar cells (PSCs) to become an industrial reality. In this work, we present two novel strategies to significantly improve the stability of PSCs using environmental humidity and down-shifting quantum dots (QDs). We first improve the crystallinity of double-cation Cs/FA perovskite by annealing films in 40% relative humidity (RH). Our results reveal that the grain size, carrier lifetime and crystallinity of perovskite films are enhanced drastically due to the humidity. Next, we apply a thin layer of CdSe/CdS quantum dots (QDs) on the back of the device to convert high energy UV light into lower energy visible wavelengths. Using this modification, we improve not only the UV stability but also the device performance of the PSCs. Based on these modifications, we achieve an inverted PSC with a maximum power conversion efficiency (PCE) of 20.7%. Moreover, our modified device shows a great operational stability under continuous illumination after 300 h with only 15% PCE loss. We also examine the UV stability of our devices and find that the modified PSC retains 79% of its initial PCE after 150 h under continuous illumination outperforming the reference device.